Optimizing Shade Level to Improve Vegetative Growth and Shoot Biomass of Patchouli (Pogostemon cablin Benth.) in Tomohon, North Sulawes. - Wanget, Sesilia Anita; Tumewu, Pemmy; Tulungen, Antje Grace; Titah, Tilda (Jurnal Agroekoteknologi Terapan (JAT), 2026)
Eco-enzyme has been promoted as a low-cost bioactivator for converting organic residues into useful soil amendments, but comparative agronomic evidence across different waste substrates remains limited. This study evaluated eco-enzyme–assisted organic fertilizers prepared from several locally available organic wastes and assessed their effects on chili pepper (Capsicum annuum L.) growth and yield in Kakaskasen, Tomohon City, North Sulawesi, Indonesia, from April to October 2025. A pot experiment was arranged in a completely randomized design with six treatments and four replications (24 experimental units). Eco-enzyme was produced by fermenting fruit peels, sugar, and water (3:1:10) for three months. Organic fertilizers were prepared using eco-enzyme alone or eco-enzyme combined with vegetable waste, fruit waste, market waste, chicken-manure waste, or household organic waste, and were incorporated into the pot medium one week before transplanting at an equivalent rate of 20 t ha⁻¹. Plant height, fruit number per plant, and fresh fruit weight per plant were measured at 100 days after transplanting and analyzed using analysis of variance followed by the least significant difference test at 5%. Organic-waste substrate significantly affected all measured variables. The eco-enzyme + market-waste formulation produced the tallest plants (133.37 cm), the highest fruit number (89.50 fruits plant⁻¹), and the highest mean fresh fruit weight (225.25 g plant⁻¹), markedly exceeding eco-enzyme alone (69.12 cm; 36.75 fruits plant⁻¹; 78.75 g plant⁻¹). Overall, eco-enzyme–activated market-waste fertilizer was the most effective formulation for improving chili growth and yield under the conditions of this pot experiment. Keywords: Capsicum annuum; eco-enzyme; market waste; organic fertilizer; waste valorization